Pendidikan Seksual Anak Usia Dini: "My Bodies Belong To Me" - Qonita Maulidya Azzahra (EARLY CHILDHOOD : JURNAL PENDIDIKAN, 2020)
Early childhood sexual education is an important thing that can be provided to children starting as early as possible. From the rampant phenomena of cases of violence and sexual harassment that often occur, this article can be a guide for readers in providing sexual education to children by paying attention to the stages of child development. This article can increase knowledge for parents in conducting sexual education about their bodies so that children can take care of themselves and prevent increasing cases of irregularities around the child. With the literature review method using various sources of research results that have been done, this article can be a reference for parents in developing knowledge about early childhood sexual education. This article explains the method of knowing the body and the rules of underwear that are packed with attention to cognitive development, communication and sexuality of children. Parents can use strategies using various methods such as storytelling, discussion or question and answer and utilizing audio, visual and audio visual communication media such as pictures, videos and songs.